International Consensus Recommendations for the Assessment and Management of Individuals With CDKL5 Deficiency Disorder - Amin, Sam; Monaghan, Marie; Aledo-Serrano, Angel; Bahi-Buisson, Nadia; Chin, Richard F.; Clarke, Angus J.; Cross, J. Helen; Demarest, Scott; Devinsky, Orrin; Downs, Jenny; Pestana Knight, Elia M.; Olson, Heather; et al. (Frontiers in Neurology, 2022)
CDKL5 Deficiency Disorder (CDD) is a rare, X-linked dominant condition that causes a developmental and epileptic encephalopathy (DEE). The incidence is between ~ 1:40,000 and 1:60,000 live births. Pathogenic variants in CDKL5 lead to seizures from infancy and severe neurodevelopmental delay. During infancy and childhood, individuals with CDD suffer impairments affecting cognitive, motor, visual, sleep, gastrointestinal and other functions. Here we present the recommendations of international healthcare professionals, experienced in CDD management, to address the multisystem and holistic needs of these individuals. Using a Delphi method, an anonymous survey was administered electronically to an international and multidisciplinary panel of expert clinicians and researchers. To provide summary recommendations, consensus was set, a priori, as >70% agreement for responses. In the absence of large, population-based studies to provide definitive evidence for treatment, we propose recommendations for clinical management, influenced by this proposed threshold for consensus. We believe these recommendations will help standardize, guide and improve the medical care received by individuals with CDD.